2007
DOI: 10.1002/art.22335
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 1 receptor as a novel therapeutic target in rheumatoid arthritis: In vivo analyses in rodent models of arthritis and ex vivo analyses in human inflammatory synovitis

Abstract: Objective. Angiotensin II (Ang II) is known to have proinflammatory actions, and Ang II type 1 (AT 1 ) receptors are up-regulated in the rheumatoid synovium, suggesting that this receptor could be a therapeutic target. The purpose of this study was to investigate the antiinflammatory potential of the selective AT 1 receptor antagonist losartan, which is currently used for the treatment of cardiovascular disease.Methods. Dose-ranging studies of losartan (1-50 mg/kg) were initially conducted in a rat model of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
49
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 36 publications
9
49
0
2
Order By: Relevance
“…2 for review). Consistent with the latter finding, blockade of AT 1 , the major receptor mediating the inflammatory actions of Ang II, reduces neutrophil recruitment and cytokine release in models of inflammation (12,37,38). However, to our knowledge, the expression of Mas receptor in periarticular tissues was demonstrated for the first time in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…2 for review). Consistent with the latter finding, blockade of AT 1 , the major receptor mediating the inflammatory actions of Ang II, reduces neutrophil recruitment and cytokine release in models of inflammation (12,37,38). However, to our knowledge, the expression of Mas receptor in periarticular tissues was demonstrated for the first time in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, blockade of Ang II may be useful in the context of inflammatory diseases, such as RA, in which a complex array of cytokines and leukocytes are involved (9). In this regard, few clinical studies have shown that Ang-converting enzyme (ACE) inhibitor (captopril) or AT 1 receptor antagonist (losartan) may be useful in the treatment of RA (10)(11)(12).…”
mentioning
confidence: 99%
“…AT1 receptor antagonists have been developed as drugs that selectively and markedly blocked the RAS at the receptor level, differently from ACE inhibitors [46]. Indeed, it has been reported that the AT1 receptor antagonist effectively attenuates various inflammatory processes [11,16,33,35]. One of the AT1 receptor blockers, telmisartan, showed a neuroprotective effect via modulating AT1 receptor and AT2 receptor signaling in retinal inflammation in a mouse EIU model [26].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have collectively demonstrated the protective effect of RAS antagonism against immunemediated inflammatory diseases such as myocarditis, chronic allograft rejection, antiglomerular basement membrane nephritis, colitis, and arthritis [1,2,6,14,15,20,22,35,38,43]. However, no report has clearly demonstrated beneficial contribution of the RAS antagonism in ocular inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…6 Similarly, the AT 1 R is upregulated in the synovium of humans with rheumatoid arthritis, another T-cell-mediated disease, and angiotensin II receptor blockade improves parameters of collagen-induced arthritis in rats and mice. 7,8 In mice with collagen-induced arthritis, angiotensin receptor blocker administration also reduces T-cell proliferation and T H 1 cytokine production. 8 An obvious question is, what does the T-cell angiotensin II receptor have to do with the disease most commonly implicated as a target of the renin angiotensin aldosterone system, ie, hypertension?…”
Section: Article See P 1604mentioning
confidence: 99%